Potato plants contain multiple forms of sucrose phosphate synthase, which differ in their tissue distributions, their levels during development, and their responses to low temperature - Sonnewald, Uwe; et al. (Plant Cell and Environment, 1997)
Antibodies raised against a peptide fragment (residues 60-456) of potato sucrose phosphate synthase (SPS) were used to investigate whether potato plants contain multiple forms of SPS. When a partially purified preparation of SPS from cold-stored potato tubers was separated on 5% polyacrylamide gel electrophoresis (PAGE), four immunopositive bands were found with estimated molecular weights of 125, 127, 135 and 145 kDa. These bands were also found in rapidly prepared extracts and were termed SPS-1a, SPS-1b, SPS-2 and SPS-3, respectively. Direct evidence that SPS-1a and SPS-1b represent active SPS was provided by the finding that both are greatly reduced in plants expressing an antisense sequence derived from the potato leaf SPS gene. SPS-2 was not decreased in the antisense plants, indicating that it has a significantly different sequence. Evidence that SPS-2 represents active SPS was obtained by showing that the amount of SPS-1a and SPS-1b protein remaining in the leaves and tubers of antisense potato plants was too low to account for the remaining SPS activity. The four immunopositive SPS forms had different tissue distributions. SPS-1a was the major form in all tissues except petals, sepals and stamens. SPS-1b and SPS-2 were absent in very young growing tissues but were present as minor forms in source leaves and sprouting tubers. The SPS-1b level was especially high in petals and sepals, and the SPS-2 level was especially high in the stamens. SPS-3 was only detected in very young tissues. The four forms also showed different responses to low temperature. Transfer of tubers to 4 degrees C led to a specific and reversible increase of SPS-1b during the next 4 d. The appearance of SPS-1b correlated with a change in the kinetic properties of SPS that has recently been shown (Hill et al. 1996) to play a key role in triggering the accumulation of sugars in cold-stored tubers. The appearance of SPS-1b protein at low temperature was accompanied by an increase of SPS transcript. Incubation of tuber slices with calyculin A and okadaic acid to alter the phosphorylation state of SPS did not lead to appearance or disappearance of SPS-1b. It is concluded that potato plants contain several forms of SPS that have different functions in growing and mature tissues, in flower parts, and in acclimation to low temperature.
Keywords: Solanum tuberosum; isoforms; low temperature; potato tuber; sucrose phosphate synthase